2021
DOI: 10.33308/26674874.2021351228
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi Öğretmen Adaylarının ve Uygulama Öğretmenlerinin Öğretmenlik Uygulaması Dersine İlişkin Görüşlerinin İncelenmesi

Abstract: Bu çalışmanın amacı okul öncesi öğretmen adaylarının ve uygulama öğretmenlerinin, Öğretmenlik Uygulaması dersine ilişkin görüşlerini incelemektir. Nitel araştırma desenlerinden olgu bilim çalışmasının kullanıldığı bu araştırmanın katılımcıları 41 okul öncesi öğretmen adayı ile 31 okul öncesi öğretmenidir. Açık uçlu görüş bildirim formu aracılığıyla toplanan veriler içerik analizi yöntemiyle analiz edilmiştir. Katılımcılara göre Öğretmenlik Uygulaması sürecinde karşılaşılan sorunlardan bazıları öğretmen adayı i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
1
1
0
3
Order By: Relevance
“…In a study by Yıldız-Altan et al ( 2018), the results showed that the feedback of the school teachers in the evaluation process of student practices was not sufficient. Similar results have been reported from the past to the present in the literature (Coşkun, 2012;Tonga & Tantekin-Erden, 2021). In a study by Göktaş and Şad (2014), it was stated that high numbers of faculty students in school classrooms could be a problem encountered in the teaching process.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 84%
“…In a study by Yıldız-Altan et al ( 2018), the results showed that the feedback of the school teachers in the evaluation process of student practices was not sufficient. Similar results have been reported from the past to the present in the literature (Coşkun, 2012;Tonga & Tantekin-Erden, 2021). In a study by Göktaş and Şad (2014), it was stated that high numbers of faculty students in school classrooms could be a problem encountered in the teaching process.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 84%
“…Bazı araştırmaların çalışma grupları yalnızca öğretmen adayları iken bazı çalışmalarda öğretmen ve öğretmen adayı ya da öğretmen ve öğretim üyelerinin (Batmaz ve Ergen, 2020) yer almaktadır. Nitekim çalışma grubu olarak uygulama öğretmeni, öğretmen adayı ve öğretim elemanından (Aslan ve Sağlam, 2018; Akgül, Ezmeci ve Akman, 2020) ya da okul yöneticilerinden (Uçar, 2012) Yılmaz, 2017;Seçer, Çeliköz ve Kayılı, 2010;Tonga ve Erden, 2021). Bununla birlikte ulaşılabilen ulusal alanyazında uzaktan eğitim sürecinde öğretmenlik uygulamasını farklı bir anabilim dalıyla karşılaştırma yapmaya olanak sağlayan bir çalışmaya rastlanmamıştır.…”
Section: Wwwkesitakademicomunclassified
“…Identified issues include ineffective time utilization, a perceived inadequacy in voice intonation and emphasis, a struggle to establish authority in the classroom, and a particular demand for improvement in the category of classroom management. Additionally, difficulties arise in maintaining control during activities designed to capture students' interest (Altintas & Gorgen, 2014;Bay et al, 2019;Ozmutlu & Tabak, 2023;Tonga & Erden, 2021). The limited opportunity for practice due to the inexperience of pre-service teachers has been identified as a contributing factor to these challenges.…”
Section: Introductionmentioning
confidence: 99%